CLINICAL EXPRESSION OF DOG OTODECTIC MANGE INVASION - Antipov, A. A.; Melnychuk, V. V.; Kovalenko, O. V.; Dolhin, O. S. (Scientific Progress & Innovations, 2020)
Otodectic mange is a quite widespread acarine disease among dogs caused by parasitizing microscopic Otodectes cynotis (Hering, 1838) ticks in the acoustic duct and on the internal concha surface. The disease causative agent has no strict species specificity that is why cats, dogs, and even fur-bearing animals suffer from otodectic mange, which spreads hosts area and is a potential source of infecting healthy animals. Young animals are especially susceptible to the invasion and they are often infected by their mother from the first days of life. As for mature animals, quite often the disease develops without any symptoms, and such animals are its spreaders. In most cases, the disease is manifested asymmetrically (only in one ear).The following general clinical signs should be singled out: the dog often tosses its head and scratches ears, there are abrasions and inflammation of cutaneous covering both on and inside the auditory passage; there is unpleasant odor from infested ears. In each separate case and at different forms of the disease development, these symptoms can vary and be more or less expressed. That is why the purpose of the study was to establish the peculiarities of the clinical picture of dog otodectic mange infestation at various forms of its development. It has been established that otodectic mange is widespread invasion on the territory of Poltava and Bila Tserkva towns – EI=20.48 %. Two forms were registered – chronic (85.53 %) and acute (14.47 %). Chronic development was characterized by reddening in the region of infested ears (100.00 %), tossing head, and appearing insignificant amounts of crusts in the concha (97.69 %), edemas and itching (90.77 and 88.46 %). Acute form was characterized by intensive itching, tossing head, reddening and soreness at ear palpation (100.00 %), as well as edemas and purulent exudation from infected ears (95.45 and 86.36 %, respectively). While studying the indices of body temperature, pulse rate and respiration, the following changes in dogs, suffering from otodectic mange have been established: at chronic disease development, temperature rise was registered to 38.64 °C (р<0.01), and at acute development – to 39.61 °C (р<0.001), on the average. Pulse rate increase was also registered to 114.80 beats/min at chronic development and 126.90 beats/min on the average at acute disease development (р<0.01 and р<0.001). It has been established that the number of respiratory movements increased on the average to 21.80 and 34.60 respiratory movements per minute, respectively, (р<0.001) in groups of dogs suffering from chronic and acute forms of otodectic mange.